APLIKASI MIKROKONTROLER BERBASIS REAL-TIME CLOCK (RTC) UNTUK AKURASI WAKTU IBADAH DI MUSHOLLA - Gaguk Firasanto; Andriani Andriani; Ronald Pakan; Raka Muhammad Hazli; Muhammad Rizky Ramadhan; Rakha Akbar Andikha (Jurnal Pengabdian kepada Masyarakat, 2026)
The primary problem faced by the Musholla congregation is the lack of accurate prayer time indicators due to manual clocks experiencing time drift, causing inconsistencies with official schedules. Additionally, there is limited interactive information media. This community service aims to implement a microcontroller-based Running Text system integrating the DS3231 Real-Time Clock (RTC) module. This module offers high precision and internal temperature compensation to maintain long-term time stability. The system automatically displays five daily prayer schedules based on geographical coordinates and serves as a dynamic information medium. The methods involved field surveys, hardware and software design, installation in the mosque, and training for mosque officials on operation and maintenance. The outcomes include a modern, accurate worship schedule system, increased congregation discipline in timely prayers, and improved information dissemination. Through this activity, the congregation directly benefits from easy access to precise worship times and the cultivation of appropriate technology utilization in a sustainable place of worship.